Integration of Lean Principles with Fuzzy FMEA in a Small Scale Casting Industry. Issue 1 (1st July 2022) - Deepan, S; Santhosh Raj, S; Ponselvan, T S; Praveenkumar, R; Alex, J.
Abstract: Economic growth of any nation is depending on the Gross Domestic Product. To improve a country economy, the industries needs to produce gross domestic products at large rate for export. Every industry has value added and non-value added (waste) activities. Non – value added activities always pulls down the efficiency, effectiveness and profit of the industry which will lets to devastating future. In order to overcome the waste many works and research has to be carried out with the focus on lean implementation. Lean implementation should be carried out progressively to obtain fruitful result. This project has been carried out on a casting industry in which non value added activities such as unnecessary transportation, motion, and waiting and high space conception are identified using current state mapping and current state layout. It is highly complicated to implement all the lean tools in a manufacturing system. So to prioritize only few lean tools which are essential to eliminate those wastes and an integrated model (combine fuzzy and FMEA environment) was used. Fuzzy is to avoid ambiguity in observation and FMEA is to prioritize the cause. After eliminating the wastes, future state value stream mapping is drawn and its performance is compared with the existing layout.